2020
DOI: 10.7759/cureus.8027
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine Level in Type I and Type II Diabetes Mellitus Patients: A Comparative Study Focusing on Hematological and Biochemical Evaluations

Abstract: Diabetes has been found to be associated with low levels of thiamine stores in the body, as thiamine directly affects carbohydrate metabolism. Amplified renal clearance of thiamine has been found in both type I and type II diabetic patients. It has been shown that high-dose thiamine therapy may have a therapeutic effect on early-stage diabetic nephropathy. The aim of this study was to evaluate various biochemical parameters and serum thiamine levels in type I and type II diabetic patients and compare them with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
(34 reference statements)
1
10
0
Order By: Relevance
“…In conclusion, TD could play an effective role in improving hyperglycemia in T1D rats [ 16 , 55 ]. TD may affect insulin and glucagon secretion by increasing the expression of genes involved in pancreatic insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, TD could play an effective role in improving hyperglycemia in T1D rats [ 16 , 55 ]. TD may affect insulin and glucagon secretion by increasing the expression of genes involved in pancreatic insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and experimental evidence has suggested that patients with insulin resistance in T1D may have abnormal glucagon action [ 3 , 15 ]. Thiamine or vitamin B1 is a coenzyme involved in the metabolism of sugars; [ 16 ] it is essential for the synthesis and secretion of insulin, and its level decreases in diabetes [ 17 , 18 ]. In thiamine deficiency, glucose is metabolized through metabolic pathways that can stimulate insulin resistance and the complications of diabetes [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, Adnan et al showed that thiamine levels were decreased in individuals with type 1 and type 2 diabetes and this may be a result of increased loss of thiamine in urine. 7 The main function of thiamine is to act as cofactor of several enzymes important for carbohydrate (transketolase [TKT], pyruvate dehydrogenase, and α-ketoglutarate dehydrogenase) and amino acid (branched-chain α-keto acid dehydrogenase) metabolism. 8 Therefore, it has been suggested that individuals with diabetes will benefit from taking thiamine supplement.…”
Section: Discussionmentioning
confidence: 99%
“…The active form of thiamine, thiamine diphosphate, is a cofactor for enzymes involved in the synthesis of neurotransmitters, antioxidants, and nucleic acids as well as for enzymes regulating glucose metabolism, such as pyruvate and oxoglutarate dehydrogenases and transketolase 283 . Patients with type 1 and type 2 diabetes mellitus have significantly decreased plasma and serum thiamine concentrations in comparison to healthy controls 284,285 . Such thiamine deficiency can reinforce hyperglycemic damage and its compensation is able to prevent the activation of pathomechanisms underlying the development of diabetic complications 286–288 …”
Section: Role Of Biofactors In Diabetes Mellitus and Its Complicationsmentioning
confidence: 99%